Color and organic matter removal from textile effluents by synthetic layered double hydroxides and natural clays - Rachid Elmoubarki; Mohamed Taoufik; Ahmed Moufti; Alaâeddine Elhalil; Fatima Zahra Mahjoubi; Mohamed Abdennouri; Mhamed Sadiq; Noureddine BARKA (Journal of Applied Surfaces and Interfaces, 2019)
This study focused on the removal of dyes and the reduction of COD of textile effluents by natural clay and a synthesized layered double hydroxide (HDL). The raw clay used in this work was collected from the region of Safi in Morocco. Mg/Fe‐LDH adsorbent was synthesized using co‐precipitation method at room temperature. Samples were characterized by XRD, SEM. The different physical and chemical parameters of the textile discharges (Electrical conductivity, TSS, COD, BOD5, NO2 and Total phosphorus) were evaluated. Experimental results showed that the maximum color and COD removal depends on the adsorbent dose and solution pH.